Product Development of Wedang Uwuh Beverage to Increase Public Interest in Planting Spices: A Practice of Regenerative Tourism in Imogiri, Yogyakarta - Dedy Setiyawan; Fitri Rahmafitria Yaman (Universitas KH. Abdul Chalim Mojokerto, 2025)
Wedang uwuh is a traditional Indonesian beverage made from a blend of local spices. The growing demand for these spices has encouraged the local community to cultivate plants used in the production of wedang uwuh. Beyond its economic benefits, cultivating these spice plants also contributes to regenerative tourism, offering mutual advantages for both the community and the environment. Social media is utilized not only to promote the product but also to enhance tourist interest by showcasing it as a unique local attraction. This study aims to explore the development of wedang uwuh products in Imogiri District. Employing a qualitative descriptive approach, this research seeks to understand and describe the experiences and phenomena encountered by the research subjects through detailed narrative data. The findings reveal that innovation in wedang uwuh product variants has significantly enhanced its branding, making it a stronger tourist attraction for both domestic and international visitors. Imogiri, as the origin area of wedang uwuh, now offers not only its natural beauty but also agro-tourism potential through community-managed spice plantations. This dual function contributes to increasing tourism appeal, improving local economic conditions, and promoting environmental preservation—an embodiment of regenerative tourism principles.